Effect of Year, Season and Parity on Milk Production Traits in Murrah Buffaloes - Pawar, Hitesh Nandlal; Ravi Kumar, Gandham; Narang, Raman (Journal of Buffalo Science, 2012)
The objective of this study was to find out the effects of year, season and parity on milk production traits i.e. total lactation milk yield (TLMY), 305 day milk yield (305d MY) and average fat percentage etc. in Murrah buffaloes under organized herd. Records of 515 Murrah buffaloes maintained at Guru Angad Dev Veterinary and Animal Sciences University (GADVASU), Ludhiana, Punjab (India) during the period of 2004-2008 were used. Average TLMY, 305d MY and fat percentage were recorded to be 2229.87± 93.7 kg, 2147.6 ± 87.06 kg and 7.12 ±0.11%. The TLMY was found to be significantly affected by season (P≤0.05) but not by year and parity. The highest milk yield was obtained in buffaloes calving in winter followed by rainy and summer. Milk yield of buffaloes in winter was significantly higher than that of animals in summer (P≤0.05). The TLMY increased over the years with highest milk yield in the year 2006 (2345.1±99.32kg). Similar results were obtained for 305d MY, where only the season was found significant (P≤0.05). The average fat percentage was significantly (P≤0.05) affected by year and season. Milk fat percentage of buffaloes calved in winter was significantly (P≤0.05) higher than that of calved in summer. Similarly milk fat percentage varied significantly among the parities with no consistent increase over the advancement of the parities. In this study season was found to have a significant effect on 305MY and fat % but not on the total lactation milk yield.